An interdisciplinary approach to regional land use analysis using GIS, with applications to the Atlantic Zone of Costa Rica - Jansen, Hans G. P.; Bouman, Bas A. M.; Schipper, Robert A.; Hengsdijk, Huib; Nieuwenhuyse, André (Wiley, 2005)
Policymakers and other stakeholders concerned with regional rural development increasingly face the need for instruments that can improve transparency in the policy debate and that enhance understanding of opportunities for and limitations to development. To this end, a methodology called SOLUS (Sustainable Options for Land Use) was developed by an interdisciplinary team of scientists over a 10-year period in the Atlantic Zone of Costa Rica. The main tools of SOLUS include a linear programming (LP) model, two expert systems that define technical coefficients for a large number of production activities, and a geographic information system (GIS). A five-step procedure was developed for GIS to spatially reference biophysical and economic parameters, to create input for the expert systems and the LP model, to store and spatially reference model output data, and to create maps of both model input and output data. SOLUS can be used to evaluate the potential effects of alternative policies and incentive structures on the performance of the agricultural sector. A number of practical applications demonstrate SOLUS’ capability to quantify trade-offs between economic objectives (income, employment) and environmental sustainability (soil nutrient balances, pesticide use, greenhouse gas emissions). GIS-created maps visualize the spatial aspects of such trade-offs and indicate hotspots where local goals may conflict with regional goals.